Vaccination in Multiple Sclerosis: Friend or Foe? - Zrzavy, Tobias; Kollaritsch, Herwig; Rommer, Paulus S.; Boxberger, Nina; Loebermann, Micha; Wimmer, Isabella; Winkelmann, Alexander; Zettl, Uwe K. (Frontiers in Immunology, 2019)
Multiple sclerosis (MS) is a debilitating disease of the central nervous systems (CNS). Disease-modifying treatments (including immunosuppressive treatments) have shown positive effects on the disease course, but are associated with systemic consequences on the immune system and may increase the risk of infections and alter vaccine efficiency. Therefore, vaccination of MS patients is of major interest. Over the last years, vaccine hesitancy has steadily grown especially in Western countries, partly due to fear of sequelae arising from vaccination, especially neurological disorders. The interaction of vaccination and MS has been discussed for decades. In this review, we highlight the immunology of vaccination, provide a review of literature and discuss the clinical consideration of MS, vaccination and immunosuppression. In conclusion, there is consensus that MS cannot be caused by vaccines, neither by inactivated nor by live vaccines. However, particular attention should be paid to two aspects: First, in immunocompromised patients, live vaccines may lead to a stronger immune reaction with signs of the disease against which the patients have been vaccinated, albeit in weakened form. Second, protection provided by vaccination should be controlled in patients who have been vaccinated while receiving immunomodulatory or immunosuppressive treatment. In conclusion, there is evidence that systemic infections can worsen MS, thus vaccination will lower the risk of relapses by reducing the risk of infections. Therefore, vaccination should be in general recommended to MS patients.